Determinants of success or failure on community forestry projects with government funding in Mexico - Martínez-Bautista, Humberto; Zamudio Sánchez, Francisco José; Alvarado-Segura, Arturo A; Ramírez Maldonado, Hugo; Fuentes Salinas, Mario (Bosque (Valdivia), 2017)
The purpose of this research was to determine the social, economic and environmental factors that influence the probability of success (failure) of timber-yielding projects under government funding in Mexico. Results are relevant for designing effective public programs focused on diminishing biodiversity loss and poverty persistence in the region. Following the scheme of community forestry in Latin America, between 2004 and 2008, the World Bank funded 96 projects in 68 Mexican communities. We focused on nine factors and their levels (explanatory variables) to explain the current status of timber-yielding projects (response variable). Our main information sources were official reports and structured interviews to people who know the community forestry program in Mexico (key informants) and chosen in a non-random way. Using association analyses, correlation, and logistic regression models, we found that social capital was the most important factor to explain both the probability of success and the one of failure. A high social capital level explained more than 43 % of success probability while low and medium social capital levels explained almost 55 % of failure probability. Furthermore, we found that the type of project is a strong determinant of success or failure; continuation of a project is not necessarily related to probability of success; and the type of social property does not determine the project success or failure. Our results agree with the theory of community forestry development.